VD_FINDINFO Arrêt / 2025 / 858 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
REJET DE LA DEMANDE, DURÉE MINIMALE DE COTISATION, AC, DÉLAI-CADRE | 13 al. 1 LACI, 8 al. 1 let. e LACI, 9 LACI, 11 OACI